A high-strength and efficient asphalt-based spherical activated carbon

By performing pyridine extraction, hydrogen peroxide treatment and nanosilicon dioxide modification on asphalt, combined with high-temperature calcination and carbonization, the existing asphalt-based spherical activated carbon has been solved, and the preparation of asphalt-based spherical activated carbon with high strength, high specific surface area and high adsorption performance has been achieved, and its application scope has been expanded.

CN117899815BActive Publication Date: 2025-03-18GUANGZHOU DIDONG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410073382.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-03-18
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

The existing asphalt-based spherical activated carbon has problems such as low strength, low surface chemical activity, small specific surface area and poor adsorption performance, which limits its application scope.

Method used

The surface oxygen-containing functional groups were increased by pulverizing and sieve the asphalt and then pyridine extraction, followed by stirring and reacting with the hydrogen peroxide solution. Next, the nano-silica is treated with ultrasonic dispersion and silane coupling agent, modified and mixed with surface-treated asphalt, calcined and carbonized at high temperature, and finally removed the silica in the hydrofluoric acid solution to obtain high-strength and efficient asphalt-based ball activated carbon.

Benefits of technology

It improves the strength, specific surface area and adsorption performance of activated carbon, expands its application range, and is suitable for water treatment, air purification, desulfurization and denitrification, and has a simple preparation method and a low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117899815B_ABST
    Figure CN117899815B_ABST
Patent Text Reader

Abstract

The invention relates to the field of activated carbon, and in particular to a high-strength and high-efficiency asphalt-based spherical activated carbon, which is used to solve the problems of low strength, low surface chemical activity, small specific surface area and poor adsorption performance of existing asphalt-based spherical activated carbon, thereby limiting the application scope thereof. After being treated with hydrogen peroxide solution, urea and sulfur powder, the high-efficiency asphalt-based spherical activated carbon can be doped with a large amount of oxygen, nitrogen and sulfur elements into the activated carbon, thereby improving its reaction activity and the adsorption effect of the activated carbon. After being treated with nano-silicon dioxide, the specific surface area, pore volume and pore size distribution inside and on the surface of the activated carbon can be increased. Therefore, while simultaneously improving the activity and specific surface area of ​​the activated carbon, the activated carbon of the invention has high strength, high specific surface area and high adsorption performance, can be used in the fields of water treatment, air purification, desulfurization and denitration, and has higher use performance and wider application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of activated carbon, and in particular to a high-strength and high-efficiency asphalt-based spherical activated carbon. Background Art

[0002] Activated carbon is a highly efficient adsorbent widely used in water treatment, air purification, desulfurization and denitrification. Asphalt-based spherical activated carbon is one of them, which is widely used because of its wide source of raw materials and simple preparation process. In the actual use of asphalt-based spherical activated carbon, the main factors affecting its performance are pore structure parameters and surface chemical properties. The pore structure mainly refers to the specific surface area, pore volume and pore size distribution of activated carbon, which determines the adsorption rate and adsorption capacity of activated carbon. The surface chemical properties mainly refer to the chemical groups on the surface of activated carbon and their distribution, such as functional groups containing oxygen, nitrogen, sulfur, etc. The surface functional groups of activated carbon, as active centers, dominate the chemical properties of the surface of activated carbon and determine its adsorption performance. However, the asphalt-based spherical activated carbon prepared by conventional methods has the problems of low strength, low surface chemical activity, small specific surface area and poor adsorption performance, which limits its application range. Therefore, it is of great practical significance to develop a high-strength and high-efficiency asphalt-based spherical activated carbon. Summary of the invention

[0003] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a high-strength and high-efficiency asphalt-based spherical activated carbon, which solves the problems of low strength, low surface chemical activity, small specific surface area and poor adsorption performance of existing asphalt-based spherical activated carbon, thereby limiting its application scope.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A high-strength and high-efficiency asphalt-based spherical activated carbon is prepared by the following steps:

[0006] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets, then add the asphalt pellets and pyridine into a Soxhlet extractor for extraction for 10-12 hours, then take it out and wash it with distilled water for 2-3 times, and then drain it naturally to obtain extracted asphalt;

[0007] Step s2: Add the extracted asphalt and hydrogen peroxide solution into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 2-3 hours at a temperature of 90-95°C and a stirring rate of 350-400r / min. After the reaction is completed, cool the reaction product to room temperature, then centrifuge it, wash the precipitate with distilled water for 2-3 times, and then place it in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3 hours to obtain surface-treated asphalt;

[0008] Step s3: placing the nano-silica in a vacuum drying oven, drying at a temperature of 150-155°C for 8-10h, then cooling and adding it to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, then adding an ethanol solution, then ultrasonically dispersing it at an ultrasonic frequency of 35-45kHz for 1-1.5h, then adding a silane coupling agent and continuing ultrasonically dispersing it for 1-1.5h, then adjusting the pH to 5-6 with glacial acetic acid, then introducing nitrogen protection and stirring the reaction at a temperature of 80-85°C and a stirring rate of 350-400r / min for 5-6h, after the reaction is completed, cooling the reaction product to room temperature, then centrifuging it, placing the precipitate in a vacuum drying oven, and drying it at a temperature of 50-55°C for 4-5h to obtain modified silica;

[0009] Step s4: adding the surface treated asphalt, modified silicon dioxide and polyvinyl alcohol aqueous solution into a three-necked flask equipped with a stirrer and a thermometer, stirring the reaction for 30-40 minutes at a temperature of 80-85°C and a stirring rate of 350-400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 50-55°C for 1-2 hours to obtain an asphalt mixture;

[0010] Step s5: placing the asphalt mixture in a tubular furnace, calcining it at a temperature of 300-320°C in an air atmosphere for 3-3.5 hours, then heating it to 600-620°C at a heating rate of 1-2°C / min, and carbonizing it in a nitrogen atmosphere for 2.5-3 hours to obtain carbonized balls;

[0011] Step s6: Mix the carbonized balls, potassium hydroxide, urea and sulfur powder evenly, then place them in a tubular furnace, calcine them at a temperature of 800-850°C and a nitrogen atmosphere for 2-3 hours, then cool them with the furnace, and then soak them in a hydrofluoric acid solution for 8-10 hours, then centrifuge them, wash the precipitate with distilled water for 2-3 times, and then place them in a vacuum drying oven, and dry them at a temperature of 80-90°C for 5-6 hours to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0012] As a further solution of the present invention: the usage ratio of the asphalt particles and pyridine in step s1 is 5g:55-60mL.

[0013] As a further solution of the present invention: the usage ratio of the extracted asphalt and the hydrogen peroxide solution in step s2 is 10g:80-90mL.

[0014] As a further solution of the present invention: the mass fraction of the hydrogen peroxide solution is 30%.

[0015] As a further solution of the present invention: the usage ratio of the nano-silica, ethanol solution and silane coupling agent in step s3 is 5g:50-60mL:0.5-2.5g.

[0016] As a further solution of the present invention: the average particle size of the nano-silicon dioxide is 15-20nm, the volume fraction of the ethanol solution is 85-90%, and the silane coupling agent is silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-792.

[0017] As a further solution of the present invention: the usage ratio of the surface treated asphalt, modified silicon dioxide and polyvinyl alcohol aqueous solution in step s4 is 10g:1-4g:40-50mL.

[0018] As a further solution of the present invention: the concentration of the polyvinyl alcohol aqueous solution is 15-18 g / L.

[0019] As a further solution of the present invention: the usage ratio of the carbonized balls, potassium hydroxide, urea and sulfur powder in step s6 is 2g:1-1.2g:1-1.2g:1-1.2g.

[0020] As a further solution of the present invention: the mass fraction of the hydrofluoric acid solution is 15-20%.

[0021] Beneficial effects of the present invention:

[0022] The high-strength and high-efficiency asphalt-based spherical activated carbon of the present invention is prepared by crushing and sieving asphalt to obtain asphalt particles, then extracting the asphalt particles and pyridine, then taking out, washing, and naturally draining to obtain extracted asphalt, stirring the extracted asphalt and a hydrogen peroxide solution for reaction, cooling the reaction product after the reaction, then centrifuging, washing and drying the precipitate to obtain surface-treated asphalt, drying the nano-silicon dioxide, then adding an ethanol solution for ultrasonic dispersion after cooling, then adding a silane coupling agent for continued ultrasonic dispersion, then adjusting the pH, then stirring the reaction, cooling the reaction product after the reaction, then centrifuging, and drying the precipitate to obtain modified silicon dioxide. Silicon oxide, surface treated asphalt, modified silicon dioxide and polyvinyl alcohol aqueous solution are stirred for reaction, after the reaction is completed, the reaction product is cooled, then centrifuged, the precipitate is dried to obtain an asphalt mixture, the asphalt mixture is placed in a tubular furnace for calcination, and then carbonized to obtain carbonized balls, the carbonized balls, potassium hydroxide, urea and sulfur powder are evenly mixed, and then placed in a tubular furnace for calcination, and then cooled with the furnace and placed in a hydrofluoric acid solution for immersion, and then centrifuged, the precipitate is washed and dried to obtain high-strength and high-efficiency asphalt-based spherical activated carbon; the high-efficiency asphalt-based spherical activated carbon is made of asphalt as raw material, and then extracted with pyridine, which can fully remove impurities in the asphalt, The extracted asphalt is obtained, and then the extracted asphalt is treated with a hydrogen peroxide solution to modify the surface of the extracted asphalt, increase the oxygen-containing functional groups such as C=O and OC=O on its surface, and enhance the activity of the activated carbon to obtain the surface-treated asphalt. The nano-silicon dioxide is then modified with a silane coupling agent to improve the dispersibility of the nano-silicon dioxide, so that it can be fully mixed with the surface-treated asphalt and evenly distributed inside the surface-treated asphalt to obtain an asphalt mixture. The asphalt mixture is then calcined and carbonized to form carbonized balls, and then the carbonized balls, potassium hydroxide, urea and sulfur powder are mixed and calcined to remove nitrogen elements, The sulfur element is effectively doped in the activated carbon, and then the silicon dioxide embedded in the activated carbon is removed with a hydrofluoric acid solution; after the high-efficiency asphalt-based ball activated carbon is treated with hydrogen peroxide solution, urea, and sulfur powder, a large amount of oxygen, nitrogen, and sulfur can be doped into the activated carbon to improve its reaction activity and the adsorption effect of the activated carbon. After being treated with nano-silicon dioxide, the specific surface area, pore volume, and pore size distribution inside and on the surface of the activated carbon can be increased. Therefore, while simultaneously improving the activity and specific surface area of ​​the activated carbon, the activated carbon of the present invention has high strength, high specific surface area, and high adsorption performance, and can be used in water treatment, air purification, desulfurization and denitrification, and other fields. At the same time, the preparation method of the present invention is simple and easy, and large-scale production can be achieved at a relatively low cost. Compared with the prior art, the present invention has higher performance and a wider application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described below in conjunction with the accompanying drawings.

[0024] Figure 1 This is a process flow chart for preparing a high-strength and high-efficiency asphalt-based spherical activated carbon in the present invention;

[0025] Figure 2 It is a Fourier transform infrared spectrum analysis diagram of the high-efficiency asphalt-based spherical activated carbon in the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1:

[0028] See also Figure 1 As shown, this embodiment is a high-strength and high-efficiency asphalt-based spherical activated carbon, which is prepared by the following steps:

[0029] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets. Then, add 5 g of the asphalt pellets and 55 mL of pyridine into a Soxhlet extractor for extraction for 10 h, then take it out and wash it twice with distilled water, and then drain it naturally to obtain extracted asphalt;

[0030] Step s2: 10 g of extracted asphalt and 80 mL of a 30% by mass hydrogen peroxide solution were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 90°C and a stirring rate of 350 r / min for 2 h. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with distilled water and then placed in a vacuum drying oven and dried at a temperature of 60°C for 2 h to obtain surface-treated asphalt;

[0031] Step s3: 5 g of nano-silicon dioxide with an average particle size of 20 nm is placed in a vacuum drying oven, dried at a temperature of 150° C. for 8 h, then cooled and added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, then 50 mL of an ethanol solution with a volume fraction of 85% is added, then ultrasonically dispersed at an ultrasonic frequency of 35 kHz for 1 h, then 0.5 g of a silane coupling agent KH-550 is added and ultrasonically dispersed for 1 h, then the pH is adjusted to 5 with glacial acetic acid, then nitrogen is introduced for protection and stirred for reaction at a temperature of 80° C. and a stirring rate of 350 r / min for 5 h, after the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 50° C. for 4 h to obtain modified silicon dioxide;

[0032] Step s4: add 10g of surface treated asphalt, 1g of modified silica and 40mL of 15g / L polyvinyl alcohol aqueous solution into a three-necked flask equipped with a stirrer and a thermometer, and stir the mixture for 30min at 80°C and 350r / min. After the reaction, cool the reaction product to room temperature, centrifuge it, place the precipitate in a vacuum drying oven, and dry it at 50°C for 1h to obtain an asphalt mixture.

[0033] Step s5: placing the asphalt mixture in a tubular furnace, calcining it at 300°C in an air atmosphere for 3 hours, then heating it to 600°C at a heating rate of 1°C / min, and carbonizing it in a nitrogen atmosphere for 2.5 hours to obtain carbonized balls;

[0034] Step s6: Mix 2g carbonized balls, 1g potassium hydroxide, 1g urea and 1g sulfur powder evenly, then place them in a tubular furnace, calcine them at 800°C in a nitrogen atmosphere for 2h, then cool them with the furnace, and then soak them in a 15% hydrofluoric acid solution for 8h, then centrifuge them, wash the precipitate twice with distilled water, and then place them in a vacuum drying oven and dry them at 80°C for 5h to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0035] Embodiment 2:

[0036] See also Figure 1 As shown, this embodiment is a high-strength and high-efficiency asphalt-based spherical activated carbon, which is prepared by the following steps:

[0037] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets. Then, add 5 g of the asphalt pellets and 58 mL of pyridine into a Soxhlet extractor for extraction for 11 hours. Then, take it out and wash it twice with distilled water, and then drain it naturally to obtain extracted asphalt;

[0038] Step s2: 10 g of extracted asphalt and 85 mL of a 30% by mass hydrogen peroxide solution were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 92°C and 380 r / min for 2.5 h. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with distilled water and then placed in a vacuum drying oven and dried at 62°C for 2.5 h to obtain surface-treated asphalt.

[0039] Step s3: 5 g of nano-silicon dioxide with an average particle size of 18 nm was placed in a vacuum drying oven, dried at a temperature of 152° C. for 9 h, then cooled and added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, then 55 mL of an ethanol solution with a volume fraction of 88% was added, and then ultrasonic dispersion was performed at an ultrasonic frequency of 40 kHz for 1.2 h, then 1.5 g of a silane coupling agent KH-560 was added and ultrasonic dispersion was continued for 1.2 h, then the pH was adjusted to 5.5 with glacial acetic acid, and then nitrogen protection was introduced and stirred for reaction at a temperature of 82° C. and a stirring rate of 380 r / min for 5.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 52° C. for 4.5 h to obtain modified silicon dioxide;

[0040] Step s4: add 10 g of surface treated asphalt, 2.5 g of modified silica and 45 mL of 17 g / L polyvinyl alcohol aqueous solution into a three-necked flask equipped with a stirrer and a thermometer, and stir the mixture for 35 min at a temperature of 82° C. and a stirring rate of 380 r / min. After the reaction is completed, cool the reaction product to room temperature, centrifuge it, place the precipitate in a vacuum drying oven, and dry it at a temperature of 52° C. for 1.5 h to obtain an asphalt mixture;

[0041] Step s5: placing the asphalt mixture in a tubular furnace, calcining it at 310°C in an air atmosphere for 3 hours, then heating it to 610°C at a heating rate of 1.5°C / min, and carbonizing it in a nitrogen atmosphere for 2.5 hours to obtain carbonized balls;

[0042] Step s6: Mix 2g carbonized balls, 1.1g potassium hydroxide, 1.1g urea and 1.1g sulfur powder evenly, then place them in a tubular furnace, calcine for 2.5h at 830°C in a nitrogen atmosphere, then cool with the furnace, and then soak them in a 18% hydrofluoric acid solution for 9h, then centrifuge, wash the precipitate with distilled water 3 times, and then place it in a vacuum drying oven and dry it at 85°C for 5.5h to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0043] Embodiment 3:

[0044] See also Figure 1 As shown, this embodiment is a high-strength and high-efficiency asphalt-based spherical activated carbon, which is prepared by the following steps:

[0045] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets, then add 5 g of the asphalt pellets and 60 mL of pyridine into a Soxhlet extractor for extraction for 12 h, then take it out and wash it with distilled water for 3 times, and then drain it naturally to obtain extracted asphalt;

[0046] Step s2: 10 g of extracted asphalt and 90 mL of a 30% by mass hydrogen peroxide solution were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 95°C and a stirring rate of 400 r / min for 3 hours. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 65°C for 3 hours to obtain surface-treated asphalt;

[0047] Step s3: 5 g of nano-silicon dioxide with an average particle size of 15 nm is placed in a vacuum drying oven, dried at a temperature of 155° C. for 10 h, then cooled and added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, then 60 mL of an ethanol solution with a volume fraction of 90% is added, and then ultrasonic dispersion is performed at an ultrasonic frequency of 45 kHz for 1.5 h, then 2.5 g of a silane coupling agent KH-792 is added and ultrasonic dispersion is continued for 1.5 h, then the pH is adjusted to 6 with glacial acetic acid, and then nitrogen protection is introduced and stirred for reaction at a temperature of 85° C. and a stirring rate of 400 r / min for 6 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain modified silicon dioxide;

[0048] Step s4: add 10g of surface treated asphalt, 4g of modified silicon dioxide and 50mL of 18g / L polyvinyl alcohol aqueous solution into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 40min at a temperature of 85°C and a stirring rate of 400r / min. After the reaction is completed, cool the reaction product to room temperature, centrifuge it, place the precipitate in a vacuum drying oven, and dry it at a temperature of 55°C for 2h to obtain an asphalt mixture;

[0049] Step s5: placing the asphalt mixture in a tubular furnace, calcining it at 320°C in an air atmosphere for 3.5 hours, then heating it to 620°C at a heating rate of 2°C / min, and carbonizing it in a nitrogen atmosphere for 3 hours to obtain carbonized balls;

[0050] Step s6: Mix 2g carbonized balls, 1.2g potassium hydroxide, 1.2g urea and 1.2g sulfur powder evenly, then place them in a tubular furnace, calcine for 3 hours at 850°C in a nitrogen atmosphere, then cool with the furnace, and then soak them in a 20% by mass hydrofluoric acid solution for 10 hours, then centrifuge, wash the precipitate with distilled water 3 times, and then place it in a vacuum drying oven and dry it at 90°C for 6 hours to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0051] Comparative Example 1:

[0052] This comparative example is a high-strength, high-efficiency asphalt-based spherical activated carbon, which is prepared by the following steps:

[0053] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets, then add 5 g of the asphalt pellets and 60 mL of pyridine into a Soxhlet extractor for extraction for 12 h, then take it out and wash it with distilled water for 3 times, and then drain it naturally to obtain extracted asphalt;

[0054] Step s2: 5 g of nano-silicon dioxide with an average particle size of 15 nm is placed in a vacuum drying oven, dried at a temperature of 155° C. for 10 h, then cooled and added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, then 60 mL of an ethanol solution with a volume fraction of 90% is added, and then ultrasonic dispersion is performed at an ultrasonic frequency of 45 kHz for 1.5 h, then 2.5 g of a silane coupling agent KH-792 is added and ultrasonic dispersion is continued for 1.5 h, then the pH is adjusted to 6 with glacial acetic acid, and then nitrogen protection is introduced and stirred for reaction at a temperature of 85° C. and a stirring rate of 400 r / min for 6 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain modified silicon dioxide;

[0055] Step s3: add 10g of extracted asphalt, 4g of modified silica and 50mL of 18g / L polyvinyl alcohol aqueous solution into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 40min at a temperature of 85°C and a stirring rate of 400r / min. After the reaction is completed, cool the reaction product to room temperature, centrifuge it, place the precipitate in a vacuum drying oven, and dry it at a temperature of 55°C for 2h to obtain an asphalt mixture;

[0056] Step s4: placing the asphalt mixture in a tubular furnace, calcining it at 320°C in an air atmosphere for 3.5 hours, then heating it to 620°C at a heating rate of 2°C / min, and carbonizing it in a nitrogen atmosphere for 3 hours to obtain carbonized balls;

[0057] Step s5: Mix 2g of carbonized balls and 1.2g of potassium hydroxide evenly, then place them in a tubular furnace, calcine for 3h at 850°C in a nitrogen atmosphere, then cool with the furnace, then soak in a 20% by mass hydrofluoric acid solution for 10h, then centrifuge, wash the precipitate with distilled water 3 times, then place it in a vacuum drying oven, and dry it at 90°C for 6h to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0058] Comparative Example 2:

[0059] This comparative example is a high-strength, high-efficiency asphalt-based spherical activated carbon, which is prepared by the following steps:

[0060] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets, then add 5 g of the asphalt pellets and 60 mL of pyridine into a Soxhlet extractor for extraction for 12 h, then take it out and wash it with distilled water for 3 times, and then drain it naturally to obtain extracted asphalt;

[0061] Step s2: 5 g of nano-silicon dioxide with an average particle size of 15 nm is placed in a vacuum drying oven, dried at a temperature of 155° C. for 10 h, then cooled and added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, then 60 mL of an ethanol solution with a volume fraction of 90% is added, and then ultrasonic dispersion is performed at an ultrasonic frequency of 45 kHz for 1.5 h, then 2.5 g of a silane coupling agent KH-792 is added and ultrasonic dispersion is continued for 1.5 h, then the pH is adjusted to 6 with glacial acetic acid, and then nitrogen protection is introduced and stirred for reaction at a temperature of 85° C. and a stirring rate of 400 r / min for 6 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain modified silicon dioxide;

[0062] Step s3: add 10g of extracted asphalt, 4g of modified silica and 50mL of 18g / L polyvinyl alcohol aqueous solution into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 40min at a temperature of 85°C and a stirring rate of 400r / min. After the reaction is completed, cool the reaction product to room temperature, centrifuge it, place the precipitate in a vacuum drying oven, and dry it at a temperature of 55°C for 2h to obtain an asphalt mixture;

[0063] Step s4: placing the asphalt mixture in a tubular furnace, calcining it at 320°C in an air atmosphere for 3.5 hours, then heating it to 620°C at a heating rate of 2°C / min, and carbonizing it in a nitrogen atmosphere for 3 hours to obtain carbonized balls;

[0064] Step s5: Mix 2g carbonized balls, 1.2g potassium hydroxide, 1.2g urea and 1.2g sulfur powder evenly, then place them in a tubular furnace, calcine for 3h at 850°C in a nitrogen atmosphere, then cool with the furnace, and then soak in a 20% by mass hydrofluoric acid solution for 10h, then centrifuge, wash the precipitate with distilled water 3 times, and then place it in a vacuum drying oven and dry it at 90°C for 6h to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0065] Comparative Example 3:

[0066] This comparative example is a high-strength, high-efficiency asphalt-based spherical activated carbon, which is prepared by the following steps:

[0067] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets, then add 5 g of the asphalt pellets and 60 mL of pyridine into a Soxhlet extractor for extraction for 12 h, then take it out and wash it with distilled water for 3 times, and then drain it naturally to obtain extracted asphalt;

[0068] Step s2: 10 g of extracted asphalt and 90 mL of a 30% by mass hydrogen peroxide solution were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 95°C and a stirring rate of 400 r / min for 3 hours. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 65°C for 3 hours to obtain surface-treated asphalt;

[0069] Step s3: 5 g of nano-silicon dioxide with an average particle size of 15 nm is placed in a vacuum drying oven, dried at a temperature of 155° C. for 10 h, then cooled and added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, then 60 mL of an ethanol solution with a volume fraction of 90% is added, and then ultrasonic dispersion is performed at an ultrasonic frequency of 45 kHz for 1.5 h, then 2.5 g of a silane coupling agent KH-792 is added and ultrasonic dispersion is continued for 1.5 h, then the pH is adjusted to 6 with glacial acetic acid, and then nitrogen protection is introduced and stirred for reaction at a temperature of 85° C. and a stirring rate of 400 r / min for 6 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain modified silicon dioxide;

[0070] Step s4: add 10g of surface treated asphalt, 4g of modified silicon dioxide and 50mL of 18g / L polyvinyl alcohol aqueous solution into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 40min at a temperature of 85°C and a stirring rate of 400r / min. After the reaction is completed, cool the reaction product to room temperature, centrifuge it, place the precipitate in a vacuum drying oven, and dry it at a temperature of 55°C for 2h to obtain an asphalt mixture;

[0071] Step s5: placing the asphalt mixture in a tubular furnace, calcining it at 320°C in an air atmosphere for 3.5 hours, then heating it to 620°C at a heating rate of 2°C / min, and carbonizing it in a nitrogen atmosphere for 3 hours to obtain carbonized balls;

[0072] Step s6: Mix 2g of carbonized balls and 1.2g of potassium hydroxide evenly, then place them in a tubular furnace, calcine for 3 hours at 850°C in a nitrogen atmosphere, then cool with the furnace, and then soak them in a 20% by mass hydrofluoric acid solution for 10 hours, then centrifuge, wash the precipitate with distilled water 3 times, and then place it in a vacuum drying oven and dry it at 90°C for 6 hours to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0073] Comparative Example 4:

[0074] This comparative example is a high-strength, high-efficiency asphalt-based spherical activated carbon, which is prepared by the following steps:

[0075] Step s1: crush the asphalt, and then pass it through a 100-mesh sieve to obtain asphalt pellets, then add 5 g of the asphalt pellets and 60 mL of pyridine into a Soxhlet extractor for extraction for 12 h, then take it out and wash it with distilled water for 3 times, and then drain it naturally to obtain extracted asphalt;

[0076] Step s2: 10 g of extracted asphalt and 90 mL of a 30% by mass hydrogen peroxide solution were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 95°C and a stirring rate of 400 r / min for 3 hours. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 65°C for 3 hours to obtain surface-treated asphalt;

[0077] Step s3: placing the surface treated asphalt in a tubular furnace, calcining it at 320°C in an air atmosphere for 3.5 hours, then heating it to 620°C at a heating rate of 2°C / min, and carbonizing it in a nitrogen atmosphere for 3 hours to obtain carbonized balls;

[0078] Step s4: Mix 2g carbonized balls, 1.2g potassium hydroxide, 1.2g urea and 1.2g sulfur powder evenly, then place them in a tubular furnace, calcine for 3h at 850°C in a nitrogen atmosphere, then cool with the furnace, and then soak in a 20% by mass hydrofluoric acid solution for 10h, then centrifuge, wash the precipitate with distilled water 3 times, and then place it in a vacuum drying oven and dry it at 90°C for 6h to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

[0079] The asphalt is medium-temperature coal asphalt provided by Anshan Iron and Steel Group Co., Ltd., and element analysis was performed on it. The analysis results are as follows:

[0080]

[0081]

[0082] The performance of the high-strength and high-efficiency asphalt-based spherical activated carbons of Examples 1-3 and Comparative Examples 1-4 was tested, and the test results are as follows:

[0083]

[0084] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the adsorption performance can be effectively improved by treatment with modified silicon dioxide, hydrogen peroxide solution, urea and sulfur powder.

[0085] The surface functional groups of the high-strength and high-efficiency pitch-based activated carbons of Example 3 and Comparative Examples 1-3 were analyzed by Fourier transform infrared spectroscopy (FT-IR). The analysis results are as follows: Figure 2 As shown:

[0086] The FT-IR adsorption spectrum of the sample of Comparative Example 1 shows a peak at 1250 cm -1 and 1600cm -1 Two absorption peaks, which can be attributed to the stretching vibration of CO bond and C=C bond respectively;

[0087] Comparison of Comparative Example 3 with Comparative Example 1 shows that the FT-IR adsorption spectrum of the sample in Comparative Example 3 is at 1057 cm -1 and 1775cm -1 Two new absorption peaks appeared at , which were mainly attributed to the stretching vibration of CO bond and C=O bond, resulting in the appearance of new carbon-oxygen bonds, which means that oxygen-containing functional groups were successfully incorporated into the activated carbon after treatment with hydrogen peroxide solution;

[0088] Comparison of Comparative Example 2 with Comparative Example 1 and Comparative Example 3 shows that the FT-IR adsorption spectrum of the sample in Comparative Example 2 does not have the same absorption peak at 1057 cm-1 as that of the sample in Comparative Example 3. -1 and 1775cm -1 There is an absorption peak at 650 cm -1 A new absorption peak appears at , which can be mainly attributed to the stretching vibration of CS bond;

[0089] Comparing Example 3 with Comparative Examples 1, 2 and 3, it is found that the FT-IR adsorption spectrum of the sample of Example 3 has a peak at 1057 cm -1 and 1775cm -1 There is also an absorption peak at 650cm -1 There is an absorption peak at 1250cm -1 and 1600cm -1 The adsorption peak at the location is more prominent than the absorption peak at the same location in the sample of Comparative Example 1, and also shows a larger wave number. This is because the stretching vibration of the CN bond and the C=N bond enhances the absorption peak here. The above information fully indicates that nitrogen and sulfur elements have been successfully incorporated into the activated carbon.

[0090] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0091] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-strength, high-efficiency pitch-based activated carbon, characterized in that: The high-efficiency asphalt-based spherical activated carbon is prepared by the following steps: Step s1: crushing and sieving the asphalt to obtain asphalt pellets, then extracting the asphalt pellets and pyridine, then taking out, washing, and naturally draining to obtain extracted asphalt; Step s2: stirring the extracted asphalt and the hydrogen peroxide solution to react, cooling the reaction product after the reaction is completed, and then centrifuging it, washing and drying the precipitate to obtain the surface-treated asphalt; Step s3: drying the nano-silicon dioxide, cooling it, adding an ethanol solution for ultrasonic dispersion, adding a silane coupling agent for continued ultrasonic dispersion, adjusting the pH, and stirring the reaction. After the reaction is completed, the reaction product is cooled, centrifuged, and the precipitate is dried to obtain modified silicon dioxide; the average particle size of the nano-silicon dioxide is 15-20 nm, the volume fraction of the ethanol solution is 85-90%, and the silane coupling agent is silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-792; Step s4: stirring the surface treated asphalt, modified silicon dioxide and polyvinyl alcohol aqueous solution for reaction, cooling the reaction product after the reaction is completed, then centrifuging and drying the precipitate to obtain an asphalt mixture; Step s5: placing the asphalt mixture in a tubular furnace for calcination, and then carbonizing it to obtain carbonized balls; Step s6: Evenly mix the carbonized balls, potassium hydroxide, urea and sulfur powder, then place them in a tubular furnace for calcination, then cool them with the furnace and soak them in a hydrofluoric acid solution, then centrifuge them, wash and dry the precipitate to obtain high-strength and high-efficiency asphalt-based spherical activated carbon.

2. A high-strength, high-efficiency pitch-based spherical activated carbon according to claim 1, characterized in that: The dosage ratio of the asphalt particles to pyridine in step s1 is 5g:55-60mL.

3. A high-strength, high-efficiency pitch-based spherical activated carbon according to claim 1, characterized in that: The usage ratio of the extracted asphalt and hydrogen peroxide solution in step s2 is 10g:80-90mL.

4. A high-strength, high-efficiency pitch-based spherical activated carbon according to claim 3, characterized in that: The mass fraction of the hydrogen peroxide solution is 30%.

5. A high-strength, high-efficiency pitch-based spherical activated carbon according to claim 1, characterized in that: The usage ratio of the nano-silica, ethanol solution and silane coupling agent in step s3 is 5g:50-60mL:0.5-2.5g.

6. A high-strength and high-efficiency pitch-based spherical activated carbon according to claim 1, characterized in that: The usage ratio of the surface treated asphalt, modified silicon dioxide and polyvinyl alcohol aqueous solution in step s4 is 10g:1-4g:40-50mL.

7. A high-strength and high-efficiency pitch-based spherical activated carbon according to claim 6, characterized in that: The concentration of the polyvinyl alcohol aqueous solution is 15-18 g / L.

8. The high-strength and high-efficiency pitch-based spherical activated carbon according to claim 1, characterized in that: The usage ratio of the carbonized balls, potassium hydroxide, urea and sulfur powder in step s6 is 2g:1-1.2g:1-1.2g:1-1.2g.

9. The high-strength and high-efficiency pitch-based spherical activated carbon according to claim 1, characterized in that: The mass fraction of the hydrofluoric acid solution is 15-20%.

Citation Information

Patent Citations

  • High-sulphur-content asphalt, high-sulphur-content activated carbon and preparation method of high-sulphur-content asphalt and high-sulphur-content activated carbon

    CN105413636A

  • Preparation method of three-dimensional graded porous spherical activated carbon material

    CN114590808A